Gawai dan the Reconstruction of Dayak Identity: A Case Study of the Dayak Gawai Festival in Sintang Regency - Markus Markus (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
This study investigates the role of Gawai Dayak Festival in Sintang as a crucial arena for thereconstruction of Dayak ethnic identity. Using a qualitative approach and case study method, data wascollected through participatory observation, in-depth interviews with traditional leaders, organizers,attendees, and visual documentation. The findings show that beyond the usual harvest thanksgivingcelebration, the Gawai Dayak Festival is utilized as a strategic platform for demonstrating both thesustainability and the evolution of Dayak culture. The festival not only visually articulates ethnic identitythrough traditional clothing, dance, and music, but also embodies political and social statements that affirmDayak presence and resistance within a context of modernization and cultural plurality. Moreover, Gawaiserves as a cultural stage for negotiating values between tradition and modernity, the sacred and thecommodified, and local and national identity. Thus, Dayak identity is presented not as something static orfixed concepts, but as a construct that is continuously changing, produced, and negotiated throughcultural practices taking place in public space. This study contributes to advancing the theoreticalunderstanding of cultural identity as a discursive and performative process embedded within contemporarysocial and political contexts. The research recommends the need to sustain such festivals due to theiressential role for indigenous communities in responding to the dynamics of modernity. Further studies canbe directed towards exploring the comparative dimension of this process across various indigenous culturalfestivals in the regional area, to obtain a more comprehensive understanding of the construction andnegotiation of cultural identity in a contemporary context.